2022
DOI: 10.1186/s10195-022-00638-7
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid reduces blood loss in primary total hip arthroplasty performed using the direct anterior approach: a one-center retrospective observational study

Abstract: Background It is still unknown whether tranexamic acid (TXA) is beneficial for the minimally invasive surgical approach to total hip arthroplasty (THA). The aim of this study is to investigate the efficacy and safety of intravenous TXA in primary THA via the direct anterior approach (DAA). Materials and methods We performed a retrospective analysis of prospectively collected data on 70 patients with nontraumatic avascular necrosis of the femoral he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 26 publications
0
3
1
Order By: Relevance
“…Concerning the absolute estimated blood loss generally, this study showed a slightly lower estimated total blood loss than described by Cao et al, who reported a loss of 744 to 1102 mL depending on the dose of tranexamic acid used perioperatively through a posterolateral approach, and by Zha et al, who reported a blood loss of 737 to 1015 mL depending on the use of tranexamic acid through a direct anterior approach [35,36].…”
Section: Discussioncontrasting
confidence: 48%
“…Concerning the absolute estimated blood loss generally, this study showed a slightly lower estimated total blood loss than described by Cao et al, who reported a loss of 744 to 1102 mL depending on the dose of tranexamic acid used perioperatively through a posterolateral approach, and by Zha et al, who reported a blood loss of 737 to 1015 mL depending on the use of tranexamic acid through a direct anterior approach [35,36].…”
Section: Discussioncontrasting
confidence: 48%
“…Vanrusselt et al also defined a LLD below 1 cm in the postoperative radiographs as a sign of successful treatment [ 38 ]. A THA perioperative blood loss of about 700 to 1200 mL is commonly reported, which roughly transfers to a hemoglobin drop of about 2 to 4 units (g/dL) [ 39 , 40 ]. The mean perioperative blood loss of this study cohort (both PA and CP groups) is therefore well in line with reported standard values of non-complex THA.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, asymptomatic DVT occurred in 2.8% of patients after DAA THA. 23 Although no direct comparison has been performed, the incidence of DVT/PE in ALS and DAA approaches may be less than that in the posterior approach.…”
Section: Discussionmentioning
confidence: 99%